Implementation of Lean Software Development Method for Developing IPOS Cashier Application in Coffee Shop - Nurhermawan, Ressa; Nugroho, Rizki; Safitri, Asih; Agustriani, Mega; Nauli, Rika Ristana; Winanti, Winanti; Sutraliyana, Marliyani; Basuki, Sucipto; Nurasiah, Nurasiah; Fuadi, Aris; Lestari, Sri (PT. BERBAGI TEKNOLOGI SEMESTA, 2025)
Cashier transactions at Coffee Shop XYZ are still done traditionally so that human error often occurs, reports are not real-time, there are still queues in payments, and financial transaction reports that have not been done quickly and accurately are problems experienced by Coffee Shop XYZ. The purpose of this paper is to develop an IPOS cashier application at Coffee Shop using the Lean method. The method used is descriptive analysis and data collection is carried out by direct interview methods with the owner and employees of Coffee Shop XYZ. A website-based IPOS cashier application is produced using the Lean method that can overcome current problems. System testing is carried out using black box testing. For the next research, the development of a mobile-based IPOS cashier application will be carried out to facilitate online ordering and payment